2018
DOI: 10.1104/pp.18.00421
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Partitioning between Glutathione and Protein Synthesis Determines Plant Growth

Abstract: Photoautotrophic organisms must efficiently allocate their resources between stress-response pathways and growth-promoting pathways to be successful in a constantly changing environment. In this study, we addressed the coordination of sulfur flux between the biosynthesis of the reactive oxygen species scavenger glutathione (GSH) and protein translation as one example of a central resource allocation switch. We crossed the Arabidopsis () GSH synthesis-depleted cadmium-sensitive mutant, which lacks glutamate cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 53 publications
4
56
0
2
Order By: Relevance
“…Clearly, this changing pattern between SnRK1 and TOR don't follow the "yin-Yang" model (Rodriguez et al 2019). It has been reported that the TOR can be activated to induce the synthesis of GSH and heat shock proteins and confer cold and drought tolerance in plants (Dobrenel et al 2013;Xiong and Sheen 2015;Bakshi et al 2017;Speiser et al 2018;Rodriguez et al 2019). This suggests that the antagonism between the SnRK1 and TOR may be ambiguous and the kinases may act in a different way under certain physiological circumstances (Rodriguez et al 2019).…”
Section: The Energy Allocation For Rice Plants To Survive In Cold Stressmentioning
confidence: 99%
“…Clearly, this changing pattern between SnRK1 and TOR don't follow the "yin-Yang" model (Rodriguez et al 2019). It has been reported that the TOR can be activated to induce the synthesis of GSH and heat shock proteins and confer cold and drought tolerance in plants (Dobrenel et al 2013;Xiong and Sheen 2015;Bakshi et al 2017;Speiser et al 2018;Rodriguez et al 2019). This suggests that the antagonism between the SnRK1 and TOR may be ambiguous and the kinases may act in a different way under certain physiological circumstances (Rodriguez et al 2019).…”
Section: The Energy Allocation For Rice Plants To Survive In Cold Stressmentioning
confidence: 99%
“…Moreover, mammalian TORC1 can directly sense nutrients such as amino acids via the activation of RAG GTPases that recruit TOR kinase to the lysosomal membrane, whereas Arabidopsis and green algae lack these RAG like GTPases and other amino acid sensors (van Dam, Zwartkruis, Bos, & Snel, 2011;Gonzalez & Hall, 2017; Kim, Goraksha-Hicks, Li, Neufeld, & Guan, 2008;Shi et al, 2018;Xiong & Sheen, 2014). Interestingly, other nutrients such as nitrogen (N), phosphate (Pi), and sulfur (S) that play an important role in plant growth and development also act via the TOR kinase pathway, thus indicating unique plant-associated sensing components that could directly or indirectly activate TOR kinase in many plant species including rice and Arabidopsis (Bakshi, Moin, Datla, & Kirti, 2017;Bakshi, Moin, Madhav, & Kirti, 2019;Couso et al, 2016;Dong et al, 2017;Mubeen, Jüppner, Alpers, Hincha, & Giavalisco, 2018;Shi et al, 2018;Speiser et al, 2018;Wu et al, 2019;Xiong & Sheen, 2015). These studies suggest that plants may have evolved unique components to regulate growth and metabolism and the detailed characterization of the same in plants is still under progress.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic sulfate is taken up from the rhizosphere into plant cells where it is reduced to sulfide and incorporated into Cys. GSH biosynthesis is the largest draw for available Cys in Arabidopsis, larger than for protein synthesis (Speiser et al ., ). The cellular concentration of GSH is closely linked to the activity of sulfate assimilation.…”
Section: Introductionmentioning
confidence: 99%